Impact of multipath delay and co-channel interference on MIMO and STBC-MIMO - Bongale, Ujwala; Patil, Vinayak; Sable, Ganesh (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
This paper presents a comparative analysis of conventional multiple-input multiple-output (MIMO) systems and space-time block coding (STBC) enhanced MIMO systems across three distinct wireless channel scenarios: flat Rayleigh fading, multipath delay, and multipath delay with co-channel interference. The ability of STBC to exploit multiple independent signal paths between the transmitter and receiver reduces the likelihood of signal fading, which is tried to represent through this work. Using MATLAB simulations, we evaluate system performance under realistic channel conditions, focusing on the key metric of bit error rate (BER). Results show that STBC significantly improves reliability and reduces BER compared to conventional MIMO, particularly under multipath and interference-laden environments.